Interrelation between the level of psychological stress and periodontal lesion - Kononova О. В. (Actual Dentistry, 2019)
Abstract. In the development of periodontal disease is important the presence of psychological stress in patients. This should be considered in the complex treatment of patients with periodontal disease. Objective. Determination of the possible relationship between the level of psychological stress in the patient’s and the presence of periodontal disease – generalized periodontitis. Material and research methods. This study was conducted on a group of 40 young patients. They were divided into the following 4 subgroups of 10 people each. First: clinically healthy individuals with no manifestations of stress with clinically healthy periodontal tissues. The second: patients with generalized periodontitis without manifestations of stress. Third: persons with manifestations of psychological stress without visible lesions of periodontal tissues. Fourth: patients with generalized periodontitis with manifestations of psychological stress. The level of psychological stress was assessed using questionnaires. All patients with generalized periodontitis were subjected to a thorough clinical examination of the oral cavity. Evaluation of the hygienic status of the oral cavity was performed using the Green-Vermillion (1964) hygienic index. To determine the degree of inflammation of the gingiva, the PMA index by C. Parma was used. Cortisol content was determined in oral fluid samples using the RP Elecsys kit (Roche Diagnostics, USA). Results. The lowest level of cortisol in saliva was found in patients without clinical signs of the disease – 14.67±2.71 nmol/l. The presence of periodontal disease slightly increases the level of cortisol to 24.33±5.47 nmol/l. In the event of psychoemotional stress, the level of cortisol increases to 29.33±2.55 nmol/l. When psychoemotional stress is combined with generalized periodontitis, the level of cortisol increases to 41.67±5.67 nmol/l. Key words: generalized periodontitis, psychoemotional stress, cortisol.